2022
DOI: 10.1038/s41598-022-07390-2
|View full text |Cite
|
Sign up to set email alerts
|

Early cardiac-chamber-specific fingerprints in heart failure with preserved ejection fraction detected by FTIR and Raman spectroscopic techniques

Abstract: The pathophysiology of heart failure with preserved ejection fraction (HFpEF) is a matter of investigation and its diagnosis remains challenging. Although the mechanisms that are responsible for the development of HFpEF are not fully understood, it is well known that nearly 80% of patients with HFpEF have concomitant hypertension. We investigated whether early biochemical alterations were detectable during HFpEF progression in salt-induced hypertensive rats, using Fourier-transformed infrared (FTIR) and Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Perivascular fibrosis appears to be low and similar between Ln and Ob rats (Figure S2e). Differently, in DSS rats 4 abundant collagen deposition was observed in both perivascular and interstitial areas. Thus, the differences between spectroscopic data obtained for the two models, are coherent with histochemical results.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Perivascular fibrosis appears to be low and similar between Ln and Ob rats (Figure S2e). Differently, in DSS rats 4 abundant collagen deposition was observed in both perivascular and interstitial areas. Thus, the differences between spectroscopic data obtained for the two models, are coherent with histochemical results.…”
Section: Discussionmentioning
confidence: 80%
“…This was indicated by the decrease of 1245 cm -1 intensity and the corresponding enhancement of 1660 cm -1 spectral component 17 . A different result was obtained for the heart tissue of a different animal model of HFpEF, induced by a high salt diet 4 . On tissues from Dsalt-sensitive (DSS) rats, an increase of intensity for the amide III band, together with a blue shift of the amide I band was assigned to the increase of collagen concentration in diseased compared to normal animals.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Differently, in DSS rats [4] abundant collagen deposition was observed in both perivascular and interstitial areas. Thus, the differences between spectroscopic data obtained for the two models, are coherent with histochemical results.…”
Section: Discussionmentioning
confidence: 80%
“…However, the application of FTIR for the assessment of hypertension-related kidney lesions has not been reported. We recently demonstrated that vibrational spectroscopic techniques are efficient diagnostic tools that are capable of detecting early chemical changes that precede the structural and functional cardiac alterations induced by prolonged hypertension [ 16 ].…”
Section: Introductionmentioning
confidence: 99%